Development and introduction of a module on medical humanities for MBBS Interns: a pedagogical experiment - Manmeet Kaur Gill; Rahul Mannan; Neha Uppal; Sahiba Kukreja; Niket Verma; Jasmine Kaur (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Loss of “empathy/ compassion” and “humanism” in undergraduate students and doctors is leading to poor patient care. The present medical curriculum has emphasis on following standardized medical “checklists” which is skewed towards treating “disease” and not “illness” (holistic approach towards both body and soul). This has led to increased patient doctor conflicts and poor patient care, which is increasingly being blamed on “burn out” for both physicians and medical students. Aim and Objectives: To develop a well-structured and validated module on medical humanities for MBBS interns and do a pilot run of the same on a group of volunteer interns to assess their knowledge and their perception regarding the same.Materials and Methods: The project was carried out at Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar, comprising of 27 MBBS interns. Need assessment was done by three rounds of Delphi culminating in developing a validated and structured module on humanities. The pilot of the module was run. Pre and Post assessments were conducted. A Feedback was also taken from the students as well as the faculty in the form of questionnaire and Focused group discussion.Results: Overall there was an increase in knowledge about medical humanities and the module was well appreciated and received by the interns, core faculty and MEU observers. No one was dissatisfied by the module. Further suggestions recommended were to increase the duration of the module by 2-3 days, making it mandatory for MBBS and rest of the clinical staff of the hospital (faculty, residents and nurses) and inclusion of a forensic expert as a part of core faculty.Conclusion: The study resulted in formation of a structured and validated module on humanities.